Kualitas Pelayanan PT. Pos Indonesia (PERSERO) Cabang Sukamerindu, Kota Bengkulu - Bambang Sutikno (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
Pos Indonesia (Persero) is one of the State-Owned Enterprises (BUMN). If the services provided by PT. Pos Indonesia (Persero) satisfies the community and has good quality, of course it will greatly help the community's economic activities and realize the welfare of the community. On the other hand, if the service provided disappoints the community and is of poor quality, it will certainly hamper the community's economic activity and have an impact on increasing poverty rates and hampering the welfare of the Indonesian people. The number of complaints about the services provided by PT. Pos Indonesia (Persero) Sukamerindu Branch, Bengkulu City is the reason why researchers conduct research on service quality at PT. Pos Indonesia (Persero) Sukamerindu Branch, Bengkulu City. The purpose of this study was to determine and analyze the quality of service at PT. Pos Indonesia (Persero) Sukamerindu Branch, Bengkulu City. This study uses a qualitative descriptive method with purposive sampling technique and with data collection techniques through observation, interviews, and documentation. Based on the results of research based on aspects of tangibles, reliability, responsiveness, assurance, empathy, adapting, and actively participating in helping develop the community's economy, it shows that: PT. Pos Indonesia (Persero) Sukamerindu Branch, Bengkulu City is of poor quality, 2. People think that employees do not serve in a friendly and polite manner. 3. People think that they have not been served quickly and responsively. 4. People think that they have not received comfort and security, 5. People feel that employees do not serve with a caring attitude, 6. Employees of PT. Pos Indonesia (Persero) Sukamerindu Branch, Bengkulu City believes that they have served the community as well as possible, but the community is often the cause of misunderstandings in the service delivery process.